Northward dispersal of dinosaurs from Gondwana to Greenland at the mid-Norian (215–212 Ma, Late Triassic) dip in atmospheric pCO2 ... - Kent, Dennis V.; Clemmensen, Lars B. (Columbia University, 2021)
The earliest dinosaurs (theropods and sauropodomorphs) are found in fossiliferous early Late Triassic strata dated to about 230 million years ago (Ma), mainly in northwestern Argentina and southern Brazil in the Southern Hemisphere temperate belt of what was Gondwana in Pangea. Sauropodomorphs, which are not known for the entire Triassic in then tropical North America, eventually appear 15 million years later in the Northern Hemi- sphere temperate belt of Laurasia. The Pangea supercontinent was traversable in principle by terrestrial vertebrates, so the main barrier to be surmounted for dispersal between hemispheres was likely to be climatic; in particular, the intense aridity of tropical desert belts and unstable climate in the equatorial humid belt accompanying high atmospheric pCO2 that characterized the Late Triassic. We revisited the chronostratigraphy of the dinosaur- bearing Fleming Fjord Group of central East Greenland and, with additional data, produced a correlation of a detailed magnetostra- ...